ANALISIS WILAYAH PELAYANAN DAN KETERSEDIAAN BARANG DI PASAR BANDAR BUAT KECAMATAN LUBUK KILANGAN KOTA PADANG - Resa Rachmawati; Yudi Antomi (JURUSAN GEOGRAFI FIS UNP, 2020)
This pupose of this study is to identify: (1) The service area of Bandar Buat Market, (2) The driving factors of buyers buy in Bandar Buat Market, (3) The origin of the supply of primary items sold at the Bandar Buat Market, and the availability of primary items sold in the Bandar Buat Market. The method of research is quantitative descriptive. Many of 45 buyers and 38 sellers in Bandar Buat Market using incidental sampling technique. Data collection techniques are done using questioner and interview guides. The research found: (1) The range of the market service includes 3 densities, which are Kecamatan Lubuk Kkilangan, Kecamatan Pauh, Kecamatam Lubuk Begalung with the farthest sample point of 5 km or further than the theoretical radius of service which is 3.5 km. (2) The factor that most encourages costumers to visit Bandar Buat Market is that they have access to 67%, the second faktor is completeness of goods (45%), the third is the quality of the goods (37%), the fourth is the price (31%), and the last is the type of the goods (20%). (3) the origin of the supplay of staple goods sold at the Bandar Buat Market originating from West Sumatera Province, especially in Padang. the availability of primary goods sold at Bandar Buat Market is sufficient to meet the daily needs of buyers.